Geometrical Comparison and Quantitative Evaluation of 18F-FDG PET/CT- and DW-MRI-Based Target Delineation Before and During Radiotherapy for Esophageal Squamous Carcinoma - Li, Huimin; Li, Jianbin; Li, Fengxiang; Zhang, Yingjie; Li, Yankang; Guo, Yanluan; Xu, Liang (Frontiers in Oncology, 2021)
Objective: This study aimed to evaluate the geometrical differences in and metabolic parameters of 18F-fluorodeoxyglucose positron emission tomography–computed tomography (18F-FDG PET–CT) and diffusion-weighted magnetic resonance imaging (DW-MRI) performed before and during radiotherapy (RT) for patients with esophageal cancer based on the three-dimensional CT (3DCT) medium and explore whether the high signal area derived from DW-MRI can be used as a tool for an individualized definition of the volume in need of dose escalation for esophageal squamous cancer. Materials and methods: Thirty-two patients with esophageal squamous cancer sequentially underwent repeated 3DCT, 18F-FDG PET–CT, and enhanced MRI before the initiation of RT and after the 15th fraction. The gross tumor volume (GTV) was delineated based on PET Edge on the first and second PET–CT images and defined as GTVPETpre and GTVPETdur, respectively. GTVDWIpre and GTVDWIdur were delineanted on the first and second DWI and corresponding T2-weighted MRI (T2W-MRI) fused images. The maximum, mean, and peak standardized uptake values (SUVs; SUVmax, SUVmean, and SUVpeak, respectively); metabolic tumor volume(MTV); and total lesion glycolysis(TLG) and its relative changes were calculated automatically on PET. the Minimum and mean apparent diffusion coefficient (ADC; ADCmin and ADCmean) and its relative changes were measured manually using ADC maps. Results: The volume of GTVCT exhibited a significant positive correlation with that of GTVPET and GTVDWI (both P<0.001). Significant differences were observed in both ADCs and 18F-FDG PET metabolic parameters before and during RT (both P<0.001). No significant correlation was observed between SUVs and ADCs before and during RT (P=0.072–0.944) and between ∆ADCs and ∆SUVs (P=0.238–0.854). The conformity index and degree of inclusion of GTVPETpre to GTVDWIpre were significantly higher than those of GTVPETdur to GTVDWIdur (both P<0.001). The maximum diameter shrinkage rate (∆LDDWI) (24%) and the tumor volume shrinkage rate (VRRDWI) (60%) based on DW-MRI during RT were significantly greater than the corresponding PET-based ∆LDPET (14%) and VRRPET (41%) rates (P=0.017 and 0.000, respectively). Conclusion: It is necessary to be cautious in the selection of boosting of the high signal area derived from DWI for an individualized definition of the volume in need of dose escalation for esophageal squamous cancer.